Ovarian and Uterine Ultrasonography in Aotus azarai infulatus - Barros Monteiro, Frederico Ozanan; Coutinho, Leandro Nassar; de Souza Pompeu, Eliane do Socorro; Gomes de Castro, Paulo Henrique; Eleuterio Maia, Celsemy; Assuncao Pereira, Washington Luis; Russiano Vicente, Wilter Ricardo [UNESP] (Springer/plenum Publishers, 2009)
We evaluated the uterus and ovaries of owl monkeys (Aotus azarai infulatus) via gynecological ultrasound examination. We evaluated the subjects in 2 different time periods. The first period (P1) was characterized by the absence of mating, with daily examinations, during 4 mo (n = 10). At the end of P1, we paired the subjects for 30 d, but without ultrasonographic evaluation. The second period (P2) was characterized by the presence of mating, with examinations once a week, during 7 consecutive months (n = 9). We evaluated the uterus and ovaries in sagittal and transverse scans, using a 5-12 MHz linear array probe. The uterine volume (UV) was directly proportional to the number of previous parturitions. The right ovary volume (RtOV) is greater than the left (LtOV) in P1 and P2. There is a positive correlation (p < 0.05) between the females' mass, RtOV (r = 0.28) and LtOV (r = 0.16).
Keywords: Aotus spp.; gynecology; New World primates; Ultrasound